Polychlorinated biphenyls and their biodegradation - Borja, Josephine Q. (Animo Repository, 2005)
Polychlorinated biphenyls (PCBs) are stable organic molecules that were widely used during 1930s and 1940s. Because of their widespread use, PCBs have entered the environment through both legal and illegal use and disposal and are persistent in the environment contaminating various environmental matrices worldwide. The environmental persistence of PCBs results primarily from the inability of natural aquatic and soil biota to metabolize the compound at a considerable rate. Several studies have been conducted on PCBs biodegradation to determine how the degradation rate can be improved. This paper is a review of literature and studies on the biodegradation of PCBs. Studies show that there are two biologically mediated PCBs degradation processes: anaerobic and aerobic. The anaerobic process removes chlorine atoms of highly chlorinated PCBs, which are then mineralized under aerobic condition. The degradation route is dependent on the complexity of the PCB congener coupled with the type of microorganism employed and the interaction among the microorganisms. © 2004 Elsevier Ltd. All rights reserved.